Ecological and human health risk of heavy metals in Nubui River: a case of rural remote communities - Norvivor, Forgive Awo; Azizi, Shohreh; Fuku, Xolile; Atibu, Emmanuel K.; Idris, Azeez Olayiwola; Sibali, Linda; Maaza, Malik; Kamika, Ilunga (Frontiers in Water, 2024)
The Nubui river is a primary source of water for drinking purpose and other domestic activities in the rural communities dotted along its riparian zone, with agriculture being the major activity occurring in this important ecotone. The river has become a potential sink for agrochemical residue, including heavy metals and has apparent aesthetic water quality issues, with associated health consequences. This study, therefore, assessed the health risks of heavy metals within the rural populations in the catchment areas, who have limited sources of improved water supply. The concentration of Iron (Fe), Lead (Pb), Cadmium (Cd), Mercury (Hg) and Zinc (Zn) was assessed on cumulatively 275 water samples, using a Perkin Elmer PINAAcle 900T atomic absorption spectrophotometer for eleven months. A cross sectional survey was conducted among 338 community members, following field observations on utilisation types, aesthetic appeal and perceived quality of water from the Nubui river. To determine the potential human and ecological risks of heavy metals, the hazard quotient, chronic daily Intake, contamination factor and health pollution indices of heavy metals were computed. STATA version 16 was used to analyse the survey results. Descriptive statistics of average concentrations of heavy metals in surface water at all sampling stations showed the pattern Hg ˂ Pb ˂ Cd ˂ Zn ˂ Fe, with relatively low concentrations, between 0.001mg/L-0.004 mg/L for Hg, 0.0011 mg/L -0.0019 mg/L for Pb, 0.0461 mg/L -0.0739 mg/L for Zn and 0.2409 mg/L -0.377 mg/L for Fe. The findings, however, showed relatively high Cadmium levels between 0.0215 mg/L -0.0383 mg/L in two out of five sampling stations in comparison to the World Health Organisation (WHO) drinking water guideline values in some months. Hazard quotient values indicate that, the population is safe from the noncarcinogenic health risks of heavy metals exposure through oral routes. Contamination factor and Heavy Metal pollution indices for Cadmium exceed recommended guideline values of 1 and 100 respectively. Meanwhile 73.1% community members evidently preferred the Nubui River for various domestic activities with 86.1% of these utilising it for drinking purposes. This occurrence, results in an exposure to associated health risks.